A case of tick-borne relapsing fever in pregnancy - Lam, John C (Can Commun Dis Rep, 2020)
Tick-borne relapsing fever (TBRF) is an infection caused by Borrelia spirochetes. In North America, Borrelia hermsii is the most common cause for TBRF. This vector-borne disease is transmitted by Ornithodoros hermsi, a soft-bodied tick found in high altitudes in northwestern United States and southwestern Canada. Once bitten by the tick and infected by B. hermsii, episodes of fever alternating with afebrile periods can occur. A case of TBRF in a pregnant host was complicated by Jarisch-Herxheimer reaction requiring critical care. This case emphasizes the importance of maintaining a high index of suspicion in TBRF. Clinician recognition, diagnosis and treatment of TBRF as well as public awareness of strategies to prevent tick bites should be strengthened.